Some Features of Cambisols Soil-forming Process from Training and Experimental Forest Range (TEFR) „Petrohan” Region. - Kameliya Petrova (Bulgarian Journal of Soil Science, 2018)
Dystric/eutric Cambisols diagnostic features from TEFR Petrohan were investigated in the present study, which morphologically corresponded to Podzols. Diagnostic horizons were investigated to establish presence or absence of podsolization process and to classify the soil type according to the modern requirements of WRB, (2006, 2007; 2014). Humus forming process insitu, clearly expressed in the Ah horizon, acidification, degradation of clay minerals, formation of E horizon, which is clay-poor with increased content of sand, accumulation of Fe and other mobile elements in Bw horizon were established. The metamorphic Bw horizon had some diagnostic properties, which met these of spodic horizon. This horizon is specific for the Podzols. The content of organic carbon in it was less than 0.5 %. Cambisols properties are predominant.It was established that the soil-forming process in the investigated Cambisols is directed to podsolization process.